Chemodynamics of Carbofuran in Cucumber - Anil Abraham (Department of Entomology, College of Agriculture, 1993)
A field experiment was conducted to study the chemodynamics of carbofuran in cucumber plants when applied as granule in the soil. The insecticide was applied at two doses of 0.5 and 1.5 kg ai/ha at three occasions viz. sowing, vining and flowering stage of the crop. The residues of carbofuran and its metabolites were estimated from the vines, leaves and fruits at different intervals after the insecticidal treatment using gas chromatographic technique. Distribution of the residues in the various portions of fruit and the effect of different periods of storage on the degradation of residues were also studied in detail. A safe waiting period was also arrived so as to avoid residue hazards in consumption of the fruits. The results indicated that absorption and metabolism of carbofuran in the plant begins soon after its application in the soil. Pure carbofuran and the metabolites, 3-OH carbofuran and 3-keto carbofuran were detected in the vines, leaves and fruit samples at 1,3,7,14,21 and 28 days after treatment. When the different portions of the plant were analysed, the highest level of residues was detected at different occasions. Thus in the vines the peak level of residues was seen on the first day after treatment where as in the leaves and fruits it was on the third seventh day respectively. A gradual decline was noticed thereafter and the residues reached almost non – detectable by 28th day after treatment in all parts of the plant. The effect of peeling on residues was studied in a separate experiment and the results indicated that peeling of fruits could reduce the residues considerably. Distibution of carbofuran residues in different fruit portions was studied and the results indicated that maximum accumulation of the residues took place in the top portions of the fruit followed by middle and basal portions. Comparing the carbofuran residues in the flesh and placenta of cucumber fruits when treated at the flowering stage of the crop it was observed that maximum accumulation of residues of carbofuran took place in the flesh portion when compared with the placenta of the fruit (inner core and seeds). Effect of storing the fruits on the degradation of carbofuran residues showed that metabolism and degradation of the chemical continued even after harvest, during the process of storage. For safe consumption of fruits following carbofuran treatment at the flowering stage a waiting period of 25 and 26 days have to be given when applied @ 0.5 and 1.5 kg ai/ha respectively.